Functor-oriented topology optimization of elasto-plastic structures. (September 2019) - Tauzowski, P.; Blachowski, B.; Lógó, J.
Highlights: The novelty of this work is related to the concept of function object called functor and its application to efficient FE code development. A novel approach to development of optimality criteria based finite element code for topology optimization of elasto-plastic structures. The programming aspects of topology optimization using traditional object-oriented and functor based programming are discussed. The advantages of the functor based approach are related to simplicity of designing the FE code architecture and reusability of this code. Abstract: The paper deals with a novel approach to development of optimality criteria based finite element code for topology optimization of elasto-plastic structures. The novelty of this work is related to the concept of function object called functor and its application to efficient FE code development. First, the general problem of topology optimization under stress constraints is briefly formulated. Then, the programming aspects of topology optimization using traditional object-oriented and functor based programming are discussed. The advantages of the functor based approach are related to simplicity of designing the FE code architecture and reusability of this code. In particular the metric known as ' Lack of cohesion of methods ' is useful in comparing these two different paradigms. Finally, the paper is also illustrated with numerical examples of topology optimization using the proposed methodology.